PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE Two Stay Two Stray (TSTS) TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PESERTA DIDIK KELAS XII MIA SMAN 1 KOTO SALAK DHARMASRAYA - Alwis Fitri Nanda (Jurnal Edukasi dan Penelitian Matematika, 2022)
The primary objective that must be met by all students in mathematics instruction is the ability to understand mathematical concepts. But as it turns out, the math comprehension skills that the students in class XII MIA SMAN 1 Koto Salak Dharmasraya possess are quite limited. This is known based on the results of a recent survey of students who were not able to provide theories that were explained in a logical manner in line with mathematical understanding indicators. It is possible to accomplish this by implementing the Two Stay Two Stray cooperative learning (TSTS). The purpose of this study is to determine whether the ability to understand matematic student is study with the use of the kooperatif type TSTS model of cooperative learning is superior to theability to understand math concept students with the use of the model of continuous learning, as well as to. Keywords– Cooperative, Two Stay Two Stray, Ability to Understand Mathematical Concepts